2021
DOI: 10.1155/2021/5547351
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Social Support between Discharge Teaching and Readiness for Discharge in Ocular Fundus Disease Patients: A Cross-Sectional Study

Abstract: Background. This study aims to evaluate the quality of discharge teaching and readiness for discharge of fundus disease patients treated with day surgery and understand the role of social support between them. Methods. This was a cross-sectional descriptive correlational survey. Through convenient sampling, fundus disease patients treated with day surgery from Zhongshan Ophthalmic Center, China, were recruited. Data were collected using demographic and disease-related information, quality of discharge teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Cronbach's α was 0.91. e Quality of Discharge Teaching Scale (QDTS) [16] measures parent perception of the quality of discharge teaching. Recognizing that parents and children receive care from multiple nurses and that discharge teaching occurs throughout the hospitalization, the 18-item QDTS tool asks the parent at the end of the hospitalization to rate the quality of teaching provided by the child's nurses on two subscales [17]. Cronbach's α was 0.82.…”
Section: Readiness For Hospital Discharge Scale and Quality Of Discha...mentioning
confidence: 99%
“…Cronbach's α was 0.91. e Quality of Discharge Teaching Scale (QDTS) [16] measures parent perception of the quality of discharge teaching. Recognizing that parents and children receive care from multiple nurses and that discharge teaching occurs throughout the hospitalization, the 18-item QDTS tool asks the parent at the end of the hospitalization to rate the quality of teaching provided by the child's nurses on two subscales [17]. Cronbach's α was 0.82.…”
Section: Readiness For Hospital Discharge Scale and Quality Of Discha...mentioning
confidence: 99%
“…Hence, adjustments to change must occur at both levels to achieve equilibrium. If nurses understand and consider family information when planning hospital discharge, they can help patients and their families be ready and well-prepared for transitions to home care [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also shown a strong relationship between RHD and social support. 7 , 20 However, Yanikkerem’s 19 study showed a weak positive correlation between them ( r = 0.270, P < 0.001).…”
Section: Introductionmentioning
confidence: 96%